PENGARUH FIRM SIZE TERHADAP TAX AVOIDANCE DENGAN VARIABEL KINERJA KEUANGAN SEBAGAI VARIABEL KONTROL - Harjanto, Gloria Mariana Kristanti; Tjahjono, Josephine Kurniawati (Politeknik Ubaya, 2025)
This study examines the influence of firm size on tax avoidance, incorporating financial performance as a control variable through profitability indicators (Return on Assets and Return on Equity), liquidity (Current Ratio), and leverage (Debt to Equity Ratio). A quantitative research method was employed, utilizing purposive random sampling on 69 corporate taxpayers registered at the KPP Pratama Makassar Utara, specifically those located in the Makassar Industrial Area (KIMA), who had fulfilled their tax obligations during the 2021–2023 period. The findings indicate that firm size, profitability, and leverage have a significant impact on tax avoidance. In contrast, liquidity does not exhibit a significant effect on tax avoidance. Future research is recommended to expand alternative proxies for the variables employed in this study, such as total revenue for firm size, Net Profit Margin for profitability, Debt to Asset Ratio for leverage, and Cash Ratio for liquidity. Furthermore, future studies may consider broadening the research scope and exploring other industries to enhance the reliability of the findings.